Cdc48/p97 promotes reformation of the nucleus by extracting the kinase Aurora B from chromatin - Ramadan, Kristijan; Bruderer, Roland; Spiga, Fabio M.; Popp, Oliver; Baur, Tina; Gotta, Monica; Meyer, Hemmo H. (Nature, 2007)
During division of metazoan cells, the nucleus disassembles to allow chromosome segregation, and then reforms in each daughter cell. Reformation of the nucleus involves chromatin decondensation and assembly of the double-membrane nuclear envelope around the chromatin; however, regulation of the process is still poorly understood. In vitro, nucleus formation requires p97 (ref. 3), a hexameric ATPase implicated in membrane fusion and ubiquitin-dependent processes. However, the role and relevance of p97 in nucleus formation have remained controversial. Here we show that p97 stimulates nucleus reformation by inactivating the chromatin-associated kinase Aurora B. During mitosis, Aurora B inhibits nucleus reformation by preventing chromosome decondensation and formation of the nuclear envelope membrane. During exit from mitosis, p97 binds to Aurora B after its ubiquitylation and extracts it from chromatin. This leads to inactivation of Aurora B on chromatin, thus allowing chromatin decondensation and nuclear envelope formation. These data reveal an essential pathway that regulates reformation of the nucleus after mitosis and defines ubiquitin-dependent protein extraction as a common mechanism of Cdc48/p97 activity also during nucleus formation.